2019
DOI: 10.1039/c9cc02580d
|View full text |Cite
|
Sign up to set email alerts
|

A COOH-terminated nitrogen-doped carbon aerogel as a bulk electrode for completely selective two-electron oxygen reduction to H2O2

Abstract: A COOH-terminated nitrogen-doped carbon aerogel exhibited 100% selectivity to two-electron oxygen reduction, exceeding reported carbonaceous and noble metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 44 publications
0
46
0
1
Order By: Relevance
“…Similar to N-doped carbon catalysts that activated π electrons and induced charge redistribution, fluorine [22,48], multiple elements [23,25], doped carbon, and metal-nonmetal co-doped carbon [24,49] also exhibited excellent performance for two-electron ORR. Zhao et al [22] discussed fluorine-doped HPC for two-electron reduction.…”
Section: Other Doped Carbonaceous Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to N-doped carbon catalysts that activated π electrons and induced charge redistribution, fluorine [22,48], multiple elements [23,25], doped carbon, and metal-nonmetal co-doped carbon [24,49] also exhibited excellent performance for two-electron ORR. Zhao et al [22] discussed fluorine-doped HPC for two-electron reduction.…”
Section: Other Doped Carbonaceous Materialsmentioning
confidence: 99%
“…As determined by DFT calculations, the interface between h-BN domains and graphene exhibited unique catalytic behavior that can preferentially drive the production of H 2 O 2 [23]. Considering the promising activity and selectivity of oxygen functional groups and the nitrogen-doping modification in decreasing the overpotential, Zhao et al [25] examined the synergistic effect of nitrogen dopants and -COOH groups on carbonaceous materials. Through theoretical calculations, the researchers found that the theoretical overpotential for two-electron ORR would be lower when the two groups combined in one carbon.…”
Section: Other Doped Carbonaceous Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying interpretation on such an abnormal phenomenon still remains a puzzle. A recent research deduced that the nitrogen doping effect on promoting the four-electron ORR can be screened by the termination of −COOH group [94] . Instead, the COOH-modified N-doped carbon exhibits a high reactivity toward two-electron ORR in alkali to produce peroxide with nearly 100% selectivity.…”
Section: Doped Nitrogen Speciesmentioning
confidence: 99%